O estado democrático brasileiro e os mecanismos de inclusão e exclusão social do adolescente em conflito com a lei - Camargo, Eduardo Martins de (2016)
This work deals with the socio-educational system and adolescents in conflict with the law in an open environment in the context of the Brazilian democratic State, seeking to answer the following question: are there mechanisms of inclusion and social exclusion acting concurrently on adolescents in conflict with the law in the democratic State Brazilian? It is divided into three chapters. The first brings a more theoretical approach on State, democracy and foundations of public policies. The second chapter presents a description of public policies aimed at adolescents in conflict with the law, especially SINASE. The third chapter deals with the mechanisms of inclusion and social exclusion of adolescents who comply with socio- educational measures; and presents data and analyzes on interviews with professionals who work in the socio-educational system of Goiânia; as well as presents data and analyzes on the field research done in medical records of adolescents in conflict with the law, of the Municipal Department of Social Assistance of Goiânia. We make use of in-depth interviews, analysis of a systematic sampling plan, data production via survey form of the Survey of the Municipal Socio-educational System in Goiânia, field diary. Keywords: State, Democracy, Public Policies, Adolescents in Conflict with the Law, Socio- educational System.